Automatic Crawling of Information to Address the Disaster Information Management - Priyadharshini, B Angeline; IlancheziaPandian, G. (IJRDO -Journal of Computer Science Engineering, 2015)
In recent years, the efficiency of sharing and managing information plays an important role in business recovery efforts after disaster event. The first issue is that reconstructing or creating information flow becomes intractable in domains. The improvement of Crisis Management and Disaster Recovery techniques are national priorities in the wake of man-made and nature inflicted. Users are eager to find valuable information to help them understand the current disaster situation and recovery status.Data mining and information retrieval techniques help impacted communities better understand the current disaster situation and how the community is recovering. Report characterization techniques generate brief reviews from a large collection of reports at different granularity. Probabilistic models with Location specific resource identification algorithm support dynamically generating query forms and information dashboard based on user feedback; and community generation and user recommendation techniques are adapted to help users identify potential contacts for report sharing and community organization.